The Influence Of Institutional Ownership, Board Of Directors Diversity And Auditor Reputation On Company Value - Suwaldiman, Suwaldiman; Abdilah, M. Betri (Cita konsultindo, 2026)
This study aims to examine the influence of institutional ownership, board of directors diversity, and auditor reputation on company value. The independent variables used in this research are institutional ownership, board of directors diversity, and auditor reputation, while the dependent variable is company value, which is measured by Tobin's Q ratio. The population in this study consists of 66 industrial companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The sample was determined using a purposive sampling method, resulting in a sample of 40 industrial companies based on specific criteria. Regression analysis is employed to test the data. The results show that institutional ownership has a significant positive effect on company value. It is interpreted that an increase in the company's share owned by institutions will drive an increase in the company’s value. In contrast, the board of directors’ diversity does not affect company value. It can be interpreted that this information is not reflected in investors' investment decisions; therefore, it has no impact on company value. Finally, auditor reputation has a significant negative effect on company value. The higher reputation of the auditor is negatively perceived by investors; therefore, it will decrease the company’s value.